Desmoplastic Fibroma of the Jaws: A Case Series and Review of Literature - Abbas Karimi; Samira Derakhshan; Monir Moradzadeh Khiavi; Farzaneh Mosavat; Faeze Mirjalili (Iranian Society of Pathology, 2020)
Desmoplastic fibroma (DF) is a benign, locally aggressive neoplasm that rarely occurs in the facial skeleton. It usually presents during the first three decades of life. Due to its aggressiveness and high recurrence rate, early diagnosis is imperative, and complete surgical removal of the lesion is the treatment of choice. Herein, we present three cases of DF namely a 2 year-old girl with a mandibular DF, a 9 year-old boy with a maxillary lesion and a 1.5-year old boy with a mandibular DF. Complete clinicopathological information, treatment plan and long-term follow-up of patients are discussed. Histopathologic features of 3 cases revealed non-capsulated spindle cell tumor with fascicular or swirling patterns in incisional biopsy. Immunohistochemical staining was performed to make a definitive diagnosis. Strongly positive nuclear immunoreactivity for β-catenin confirmed the diagnosis of desmoplastic fibroma in 3 cases. Segmental mandibulectomy, partial maxillectomy and hemimandibulectomy were done for the cases. There was no recurrence in our reported cases after 8 and 11 months and 3 years follow up, respectively. It is noteworthy that despite the aggressive nature of DF, young patients often respond well to wide resection treatment.